(untitled) (Revista Brasileira Multidisciplinar, 2026)
Health care for people with spinal cord injury in Primary Health Care (PHC) is fundamental, as it is the coordinator of care and the preferred gateway to the network. However, rehabilitation services are still allocated as the center of the Care Network for People with Disabilities. Studies that highlight the role of other points in this network and contribute to articulated health care that is sensitive to the demands of this population are important. This study aimed to investigate the knowledge of PHC professionals regarding health care provided to people with spinal cord injuries in this context, in Macaíba, Rio Grande do Norte. This is an exploratory study, with a mixed approach. A semi-structured questionnaire was used for data collection, with the participation of 20 PHC professionals from the municipality. The data underwent content analysis and the following categories emerged: 1) Network; 2) Environment; 3) Organization and Work in Health; 4) Social Support; 5) Strengthening Communication; 6) Educational Strategies. The main finding was that PHC professionals have incipient knowledge about care for these users in PHC and little understanding of the barriers and facilitators that exist in the care of people with spinal cord injuries in the territory. Weaknesses in communication between the network services were observed. It is necessary to carry out ongoing health education activities on spinal cord injuries and other structural themes related to disability, which may reflect in the qualification and adequate care for these people.